Financial Transaction Tax and Financial Market Stability with Diverse Beliefs - Jörg Rieger (University of Heidelberg, Department of Economics, 2014)
This papers studies the impact of a financial transactions tax on the trading volume and asset price volatility in a model with heterogeneous beliefs. To model heterogeneous beliefs we follow Kurz (1994, 1997) and restrict the class of beliefs to the subset of rational beliefs. We study a tax on bond and asset purchases. The simulated model shows that the introduction of a transaction tax results in a lower trading volume and therefore in less liquid financial markets. Because of the decreased liquidity the volatility of the stock market increases. We also study the welfare effects of a financial transaction tax and the simulation results also show that there is only a small change in welfare.
urn:nbn:de:bsz:16-heidok-168044
Keywords: 330; Transaction Tax; Financial Regulation; Heterogeneous Beliefs